마이크로버블과 환원제를 이용한 습식 NO 및 SO₂의 동시제거 - 송동훈(Dong Hun Song); 강조홍(Jo Hong Kang); 박현식(Hyun Sic Park); 송호준(Hojun Song); 정용철(Yongchul G. Chung) (Clean Technology, 27(4), 2021)
연소시설에서는 화석연료에 포함된 질소와 황이 산소와 반응하여 대기 오염물질인 질소산화물(NOX)과 황산화물(SOX)을 발생시킨다. 인체에 유해하고 환경 오염을 야기하는 NOX, SOX를 저감하기 위해 전세계적으로 환경규제를 시행 중이며, 규제를충족하기 위해 다양한 기술들을 적용하고 있다. 상용화된 NOX 및 SOX 저감방식들로 SCR (selective catalytic reduction),SNCR (selective non-catalytic reduction), WFGD (wet flue gas desulfurization) 등이 있으나 이 방식들의 단점들 때문에 NOX,SOX를 동시제거하는 연구가 근래 많이 수행되고 있다. 그러나 NOX, SOX 동시 제거 방식에서도 산화제 및 흡수제로 인한 폐수 발생에 대한 문제점, 특정 산화제를 활성화 하기 위한 촉매 및 전기분해 사용에 따른 비용 발생, 마지막으로 기체 산화제들자체 유해성의 문제점을 가지고 있다. 따라서 본 연구에서는 NOX, SOX 동시처리 방식의 단점들을 보완하고자 고압분산기에서 생성된 마이크로버블과 환원제를 이용하여 비용절감 및 폐수처리 시 환경부하저감 가능성을 확인해 하고자 하였다. 분산기가 마이크로버블을 생성하는 것을 이미지 프로세싱과 ESR (electron spin resonance) 분석을 통해 확인하였으며, 마이크로버블만을 이용하여 온도에 따른 NOX, SOX 제거율 성능 테스트도 진행하였다. 뿐만 아니라 폐수를 저감하기 위해 환원제와 마이크로버블을 이용하여 습식으로 NOX 제거율 약 75%, SOX 제거율 99%를 달성하였다. 본 마이크로버블 시스템에 산화제를함께 투여할 경우 NOX, SOX제거율 모두 99%이상을 달성 하였다. 이러한 연구 결과를 토대로 습식산화제거방식을 적용하는시설의 단점이었던 비용 및 환경 문제를 해결함에 기여할 수 있을 것으로 기대 된다. In combustion facilities, the nitrogen and sulfur in fossil fuels react with oxygen to generate air pollutants such asnitrogen oxides (NOX) and sulfur oxides (SOX), which are harmful to the human body and cause environmental pollution. Thereare regulations worldwide to reduce NOX and SOX, and various technologies are being applied to meet these regulations. Thereare commercialized methods to reduce NOX and SOX emissions such as selective catalytic reduction (SCR), selectivenon-catalytic reduction (SNCR) and wet flue gas desulfurization (WFGD), but due to the disadvantages of these methods, manystudies have been conducted to simultaneously remove NOX and SOX. However, even in the NOX and SOX simultaneous removalmethods, there are problems with wastewater generation due to oxidants and absorbents, costs incurred due to the use of catalystsand electrolysis to activate specific oxidants, and the harmfulness of gas oxidants themselves. Therefore, in this research,microbubbles generated in a high-pressure disperser and reducing agents were used to reduce costs and facilitate wastewater treatment in order to compensate for the shortcomings of the NOX, SOX simultaneous treatment method. It was confirmedthrough image processing and ESR (electron spin resonance) analysis that the disperser generates real microbubbles. NOX andSOX removal tests according to temperature were also conducted using only microbubbles. In addition, the removal efficienciesof NOX and SOX are about 75% and 99% using a reducing agent and microbubbles to reduce wastewater. When a small amount ofoxidizing agent was added to this microbubble system, both NOX and SOX removal rates achieved 99% or more. Based on thesefindings, it is expected that this suggested method will contribute to solving the cost and environmental problems associated withthe wet oxidation removal method. KCI Citation Count: 0